Peran Lingkungan Belajar terhadap Perkembangan Sosial Anak (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study examines the role of the learning environment in shaping children’s social development from early childhood to primary school years. The research aims to explain how social interactions, teacher and parent involvement, and classroom climate contribute to children’s social competencies within both formal and non-formal educational settings. Using a descriptive qualitative approach through library research, data were collected from scholarly articles, academic books, and reputable research reports. Content analysis was applied to identify recurring patterns and thematic relationships across the literature. The findings indicate that a positive learning environment significantly enhances children’s social abilities, including communication skills, empathy, cooperation, and emotional regulation. Interactions among peers, supportive teaching practices, and an emotionally safe classroom climate emerged as essential determinants of social development. The study highlights the multidimensional nature of the learning environment and underscores its implications for educational practice. It suggests that teachers, schools, and parents must collaboratively create inclusive and supportive learning settings to optimize children’s social growth. This study also emphasizes the need for future empirical research to validate the conceptual findings derived from literature-based analysis.